Learning to be a mother: Comparing two groups of Chinese immigrants in the Netherlands. (June 2019) - Zheng, Lijie; de Haan, Mariëtte; Koops, Willem
Immigrant parents may have to rebuild their parenting knowledge after migration to keep up with their new milieu. Comparing two subgroups of Chinese immigrants, economic and knowledge immigrants, this study shows that the construction of different parental ethnotheories can be understood through the characteristics of their parenting knowledge acquisition, social networks and networking strategies. Findings from ego-network interviews with 15 economic immigrant mothers and 20 knowledge immigrant mothers indicate that the former tends to obtain practical tips and specific instructions directly from experts and acquire practical help from local, co-ethnic, small and dense networks, while the latter engages in critical peer-based learning in multicultural, open and long-distance networks. This study argues that a social network perspective can shed light on the "black box" of how parenting theories are reconstructed after migration.